The Integration of Guided Question Technique in Oral Presentation Method to Improve Students Speaking Ability - Khadijah Maming; Badaruddin; Anisa Meifa Anton (Eduvelop: Journal of English Education and Development, 2023)
This research aims to know the integration of guided question technique in oral presentation method on students’ speaking ability at the second grade students of UPTD SMPN 1 Parepare. Many students had low in speaking due to lack of practice and lack of enthusiasm in studying English, therefore the students had no idea and confused about what they were going to say or speak. The researchers used a quasi-experimental method with a two-group design. The researchers used cluster random sampling and divided the students into two groups namely experimental group and control group. Each group consisted of twenty three students. In collecting the data with pretest and posttest, the form was an oral test and four meetings for the treatment. The technique of analysis data used mean score and t-test formula for an independent sample. The result of the data analysis showed there was an improvement in students’ speaking ability. The mean score of experimental class posttest was 76.04 and the mean score of control class was 71. Therefore, the end result was 2.389 > 1.680 means that was higher than and was rejected while was accepted. It can be concluded that the integration of guided question technique in oral presentation method improved speaking ability of the second grade students of UPTD SMPN 1 Parepare. The researchers concluded that by the integration of guided question technique in oral presentation method can help the students to overcome their problems and also made students spoke communicatively during presentations.